THE MEAN REMAINING STRENGTH OF PARALLEL SYSTEMS IN A STRESS-STRENGTH MODEL BASED ON EXPONENTIAL DISTRIBUTION - KIZILASLAN, FATİH (ANKARA UNIV, FAC SCI, 2019)
The mean remaining strength of any coherent system is one of the important characteristics in stress-strength reliability. It shows that the system on the average how long can be safe under the stress. In this paper, we consider the mean remaining strength of the parallel systems in the stress-strength model. We assume that the strength and stress components constitute parallel systems separately. The mean remaining strength and its estimations are obtained when the all components follow the exponential distribution. The likelihood ratio order between the remaining strength of the parallel systems is presented for two-component case. The simulation study is performed to compare the derived estimates and their results are presented.
Keywords: Mean remaining strength; exponential and generalized exponential distributions; stress-strength model; RELIABILITY